2020
DOI: 10.2337/cd19-0030
|View full text |Cite
|
Sign up to set email alerts
|

“What’s the Point?”: Understanding Why People With Type 2 Diabetes Decline Structured Education

Abstract: Structured diabetes education (SDE) is an evidencebased intervention that supports self-management in people with type 2 diabetes. In the United Kingdom, health care providers working in primary care settings are responsible for referring people with type 2 diabetes to SDE programs. However, national audits record a high percentage of nonattenders. We explored the personal experience of living with type 2 diabetes that led to individuals declining invitations to attend SDE programs. The themes suggested that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…This finding is congruent with the ‘ enabling factors’ category of ABM which outlines that the availability and nature of support can facilitate or impede health service utilisation [ 19 ]. However, it contrasts with previous findings in the field which have found lack of support and poor physician-patient relationships as barriers to attendance [ 32 ]. Our findings may be explained by a study by Gucciardi and colleagues [ 33 ] which found that some individuals perceive primary care physicians to provide the same coverage of diabetes education and lifestyle modification skills training as DSME.…”
Section: Discussioncontrasting
confidence: 90%
“…This finding is congruent with the ‘ enabling factors’ category of ABM which outlines that the availability and nature of support can facilitate or impede health service utilisation [ 19 ]. However, it contrasts with previous findings in the field which have found lack of support and poor physician-patient relationships as barriers to attendance [ 32 ]. Our findings may be explained by a study by Gucciardi and colleagues [ 33 ] which found that some individuals perceive primary care physicians to provide the same coverage of diabetes education and lifestyle modification skills training as DSME.…”
Section: Discussioncontrasting
confidence: 90%
“…11,14 The key role that GPs and other frontline professionals play has also been identified in other research on attendance at Type 2 diabetes education programmes. [31][32][33][34] One of the strengths of this study is collection of data from a high number of non-attenders, who are usually difficult to recruit. 1,15 We also recruited a sample including individuals from a socioeconomically deprived area, which is a known risk factor for T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative working between community and clinical services is needed to ensure programmes like the NHSDPP are effectively implemented 11,14 . The key role that GPs and other frontline professionals play has also been identified in other research on attendance at Type 2 diabetes education programmes 31‐34 …”
Section: Discussionmentioning
confidence: 99%
“…Diabetes education has also been a focus of many prior studies. Diabetes education is a specific intervention that supports diabetes self-management [ 19 ]. A systematic review and meta-analysis indicate that diabetes education improves clinical, lifestyle, and psychological outcomes for type-2 diabetic patients compared to usual care [ 20 ].…”
Section: Related Workmentioning
confidence: 99%